The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1471-0528.14608
|View full text |Cite
|
Sign up to set email alerts
|

Fibroid vascularisation assessed with three‐dimensional power Doppler ultrasound is a predictor for uterine fibroid growth: a prospective cohort study

Abstract: Fibroid vascularisation correlates with absolute fibroid volume change and fibroid growth rate per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…This may be because fibroids with significant enhancement are more vascular; blood flow in vascular fibroids could dissipate some heat and therefore the acoustic energy deposition in these fibroids is less than that of avascular uterine fibroids [9,10]. Recently, Nieuwenhuis et al found that the growth rate of fibroids was related to the proportion of blood vessels within the fibroid tissue [11]. Therefore, after HIFU, the residual tumor tissue in vascular fibroids (significant enhancement) is more likely to grow faster than that in avascular fibroid tumors (less enhancement).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because fibroids with significant enhancement are more vascular; blood flow in vascular fibroids could dissipate some heat and therefore the acoustic energy deposition in these fibroids is less than that of avascular uterine fibroids [9,10]. Recently, Nieuwenhuis et al found that the growth rate of fibroids was related to the proportion of blood vessels within the fibroid tissue [11]. Therefore, after HIFU, the residual tumor tissue in vascular fibroids (significant enhancement) is more likely to grow faster than that in avascular fibroid tumors (less enhancement).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fibroids close to the uterine cavity (type 3) interferes with endometrial blood flow. In a prospective study, Niewenhuis et al [ 31 ] showed that the increase in myoma volume was greater in highly vascularized myomas, strongly supporting the notion that blood supply modifications may affect blastocyst implantation, as suggested by Schild et al [ 32 ] and Kim et al [ 33 ].…”
Section: Infertilitymentioning
confidence: 74%
“…The vessels in the fibroid tissue lack the normal structure compared to the myometrial vessels and are more narrow in diameter [18]. Most fibroids are surrounded by a highly vascularized pseudocapsule which has its own gene expression profile and supplies the fibroid with peri-and intra-fibroid arteries [19]. Oxytocin mainly exerts its effects through the oxytocin receptor, which has a tissue-specific expression pattern.…”
Section: Discussionmentioning
confidence: 99%